Observing gravitational-wave transient GW150914 with minimal assumptions - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Abernathy, M. R.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, P.; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; et al. (Amer Physical Soc, 2016)
The gravitational-wave signal GW150914 was first identified on September 14, 2015, by searches for short-duration gravitational-wave transients. These searches identify time-correlated transients in multiple detectors with minimal assumptions about the signal morphology, allowing them to be sensitive to gravitational waves emitted by a wide range of sources including binary black hole mergers. Over the observational period from September 12 to October 20, 2015, these transient searches were sensitive to binary black hole mergers similar to GW150914 to an average distance of similar to 600 Mpc. In this paper, we describe the analyses that first detected GW150914 as well as the parameter estimation and waveform reconstruction techniques that initially identified GW150914 as the merger of two black holes. We find that the reconstructed waveform is consistent with the signal from a binary black hole merger with a chirp mass of similar to 30 M-circle dot and a total mass before merger of similar to 70 M-circle dot in the detector frame.